2011
DOI: 10.1111/j.1728-4457.2011.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Television and Radio with Reproductive Behavior

Abstract: This note analyzes the association between media exposure and reproductive behavior in 48 developing countries. A summary of part of a more extensive Demographic and Health Surveys report, it shows strong connections between media exposure and the use of modern contraception, the number of children desired, and recent fertility. Television viewing is particularly important; it is assumed to expose viewers to aspects of modern life that compete with traditional attitudes toward the family and is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 5 publications
4
36
0
Order By: Relevance
“…The urban-rural divide regarding reproductive health behaviour is explainable by the fact that people in urban areas tend to have higher literacy and socioeconomic status, enjoy better access to healthcare service and receives greater media exposure, all of which are likely to improve health behaviour in general [32, 33]. In our study, men who reported having the habit of reading newspaper occasionally or regularly had higher participation in reproductive care.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 73%
See 1 more Smart Citation
“…The urban-rural divide regarding reproductive health behaviour is explainable by the fact that people in urban areas tend to have higher literacy and socioeconomic status, enjoy better access to healthcare service and receives greater media exposure, all of which are likely to improve health behaviour in general [32, 33]. In our study, men who reported having the habit of reading newspaper occasionally or regularly had higher participation in reproductive care.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 73%
“…Despite that, TV and radio programs remain a source of entertainment and pastime for many. In China, watching television was found to be strongly associated with adoption of modern contraceptive methods and the number of children desired [33]. As the population in Bangladesh is predominantly rural, the media sector should take innovative actions to design TV/radio entertainments more interesting and effective by incorporating health messages into age specific programs to encourage positive attitude towards reproductive health.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…Social influence was defined as any mention by the patient or provider of influence from any member of the patient's social network (a friend, family member, coworker or partner) or the media (online, TV or radio) with regards to contraception. Media was included in the analysis of social influence because it is a non-clinical source of patient information with documented effect on contraceptive use (Westoff & Koffman, 2011). Visits were also coded regarding whether mention of social influence had been patient or provider-initiated.…”
Section: Methodsmentioning
confidence: 99%
“…There are many complex factors that have been studied as influences on women's contraceptive use, including knowledge about contraception, pregnancy intentions, and concerns about side effects and safety (Carter, Bergdall, Henry-Moss, Hatfield-Timajchy, & Hock-Long, 2012; Cheung & Free, 2005; Crosby, 2002; Frost & Darroch, 2008; Gilliam, Warden, Goldstein, & Tapia, 2004; Jaccard & Dodge, 2003; Ryan, Franzetta, & Manlove, 2007; Schunmann, 2006; Zapata, Steenland, Brahmi, Marchbanks, & Curtis, 2012). An additional factor that has begun to receive attention is the role of women's social context on contraceptive behavior (Ali, Amialchuk, & Dwyer, 2011; Blackstock, Mba-Jonas, & Sacajiu, 2010; Carter et al, 2012; Gayen & Raeside, 2010; Valente, Watkins, Jato, van der Straten, & Tsitsol, 1997; Westoff & Koffman, 2011). Social context includes the members of the woman's social network (friends, family, partners), as well as her exposure to various media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation